How bacterial pathogens of the gastrointestinal tract use the mucosal glyco-code to harness mucus and microbiota: New ways to study an ancient bag of tricks - Christine Josenhans; Johannes Müthing; Lothar Elling; Sina Bartfeld; Herbert Schmidt (Elsevier, 2020)
During the last decades, the flourishing scientific field of molecular pathogenesis brought groundbreaking knowledge of the mechanisms of pathogenicity and the underlying bacterial virulence factors to cause infectious diseases. However, a major paradigm shift is currently occurring after it became increasingly evident that bacterial-host and host-host cell interactions including immune responses orchestrated by defined virulence factors are not the sole drivers of infectious disease development. Strong evidence has been collected that information and nutrient flow within complex microbial communities, as well as to and from host cells and matrices are equally important for successful infection. This particularly holds true for gastrointestinal (GI) pathogens and the GI microbiota interacting and communicating with each other as well as with the host GI mucus and mucosa. Gut-adapted pathogens appear to have developed powerful and specific strategies to interact with human GI mucus including the microbiota for nutrient acquisition, mucosal adhesion, inter-species communication and traversing the mucus barrier. This review covers the existing evidence on these topics and explores the mutual dynamics of host GI mucus, the mucosal habitat and incoming acute and chronic pathogens during GI infections. A particular focus is placed on the role of carbohydrates in diverse mucosal interaction, communication and competition processes. Novel techniques to analyze and synthesize mucus-derived carbohydrates and to generate mucus mimetics are introduced. Finally, open questions and future objectives for pathogen - host GI mucus research will be discussed.